module plfa.part1.Isomorphism where

This section introduces isomorphism as a way of asserting that two types are equal, and embedding as a way of asserting that one type is smaller than another. We apply isomorphisms in the next chapter to demonstrate that operations on types such as product and sum satisfy properties akin to associativity, commutativity, and distributivity.


import Relation.Binary.PropositionalEquality as Eq
open Eq using (_≡_; refl; cong; cong-app)
open Eq.≡-Reasoning
open import Data.Nat using (; zero; suc; _+_)
open import Data.Nat.Properties using (+-comm)

Lambda expressions

The chapter begins with a few preliminaries that will be useful here and elsewhere: lambda expressions, function composition, and extensionality.

Lambda expressions provide a compact way to define functions without naming them. A term of the form

λ{ P₁ → N₁; ⋯ ; Pₙ → Nₙ }

is equivalent to a function f defined by the equations

f P₁ = N₁
f Pₙ = Nₙ

where the Pₙ are patterns (left-hand sides of an equation) and the Nₙ are expressions (right-hand side of an equation).

In the case that there is one equation and the pattern is a variable, we may also use the syntax

λ x → N


λ (x : A) → N

both of which are equivalent to λ{x → N}. The latter allows one to specify the domain of the function.

Often using an anonymous lambda expression is more convenient than using a named function: it avoids a lengthy type declaration; and the definition appears exactly where the function is used, so there is no need for the writer to remember to declare it in advance, or for the reader to search for the definition in the code.

Function composition

In what follows, we will make use of function composition:
_∘_ :  {A B C : Set}  (B  C)  (A  B)  (A  C)
(g  f) x  = g (f x)
Thus, g ∘ f is the function that first applies f and then applies g. An equivalent definition, exploiting lambda expressions, is as follows:
_∘′_ :  {A B C : Set}  (B  C)  (A  B)  (A  C)
g ∘′ f  =  λ x  g (f x)


Extensionality asserts that the only way to distinguish functions is by applying them; if two functions applied to the same argument always yield the same result, then they are the same function. It is the converse of cong-app, as introduced earlier.

Agda does not presume extensionality, but we can postulate that it holds:
  extensionality :  {A B : Set} {f g : A  B}
     (∀ (x : A)  f x  g x)
     f  g

Postulating extensionality does not lead to difficulties, as it is known to be consistent with the theory that underlies Agda.

As an example, consider that we need results from two libraries, one where addition is defined, as in Chapter Naturals, and one where it is defined the other way around.
_+′_ :     
m +′ zero  = m
m +′ suc n = suc (m +′ n)
Applying commutativity, it is easy to show that both operators always return the same result given the same arguments:
same-app :  (m n : )  m +′ n  m + n
same-app m n rewrite +-comm m n = helper m n
  helper :  (m n : )  m +′ n  n + m
  helper m zero    = refl
  helper m (suc n) = cong suc (helper m n)
However, it might be convenient to assert that the two operators are actually indistinguishable. This we can do via two applications of extensionality:
same : _+′_  _+_
same = extensionality  m  extensionality  n  same-app m n))

We occasionally need to postulate extensionality in what follows.

More generally, we may wish to postulate extensionality for dependent functions.
  ∀-extensionality :  {A : Set} {B : A  Set} {f g : ∀(x : A)  B x}
     (∀ (x : A)  f x  g x)
     f  g

Here the type of f and g has changed from A → B to ∀ (x : A) → B x, generalising ordinary functions to dependent functions.


Two sets are isomorphic if they are in one-to-one correspondence. Here is a formal definition of isomorphism:
infix 0 _≃_
record _≃_ (A B : Set) : Set where
    to   : A  B
    from : B  A
    from∘to :  (x : A)  from (to x)  x
    to∘from :  (y : B)  to (from y)  y
open _≃_

Let’s unpack the definition. An isomorphism between sets A and B consists of four things:

  1. A function to from A to B,
  2. A function from from B back to A,
  3. Evidence from∘to asserting that from is a left-inverse for to,
  4. Evidence to∘from asserting that from is a right-inverse for to.

In particular, the third asserts that from ∘ to is the identity, and the fourth that to ∘ from is the identity, hence the names. The declaration open _≃_ makes available the names to, from, from∘to, and to∘from, otherwise we would need to write _≃ and so on.

The above is our first use of records. A record declaration behaves similar to a single-constructor data declaration (there are minor differences, which we discuss in Connectives):
data _≃′_ (A B : Set): Set where
  mk-≃′ :  (to : A  B) 
           (from : B  A) 
           (from∘to : (∀ (x : A)  from (to x)  x)) 
           (to∘from : (∀ (y : B)  to (from y)  y)) 
          A ≃′ B

to′ :  {A B : Set}  (A ≃′ B)  (A  B)
to′ (mk-≃′ f g g∘f f∘g) = f

from′ :  {A B : Set}  (A ≃′ B)  (B  A)
from′ (mk-≃′ f g g∘f f∘g) = g

from∘to′ :  {A B : Set}  (A≃B : A ≃′ B)  (∀ (x : A)  from′ A≃B (to′ A≃B x)  x)
from∘to′ (mk-≃′ f g g∘f f∘g) = g∘f

to∘from′ :  {A B : Set}  (A≃B : A ≃′ B)  (∀ (y : B)  to′ A≃B (from′ A≃B y)  y)
to∘from′ (mk-≃′ f g g∘f f∘g) = f∘g

We construct values of the record type with the syntax

  { to    = f
  ; from  = g
  ; from∘to = g∘f
  ; to∘from = f∘g

which corresponds to using the constructor of the corresponding inductive type

mk-≃′ f g g∘f f∘g

where f, g, g∘f, and f∘g are values of suitable types.

Isomorphism is an equivalence

Isomorphism is an equivalence, meaning that it is reflexive, symmetric, and transitive. To show isomorphism is reflexive, we take both to and from to be the identity function:
≃-refl :  {A : Set}
   A  A
≃-refl =
    { to      = λ{x  x}
    ; from    = λ{y  y}
    ; from∘to = λ{x  refl}
    ; to∘from = λ{y  refl}

In the above, to and from are both bound to identity functions, and from∘to and to∘from are both bound to functions that discard their argument and return refl. In this case, refl alone is an adequate proof since for the left inverse, from (to x) simplifies to x, and similarly for the right inverse.

To show isomorphism is symmetric, we simply swap the roles of to and from, and from∘to and to∘from:
≃-sym :  {A B : Set}
   A  B
   B  A
≃-sym A≃B =
    { to      = from A≃B
    ; from    = to   A≃B
    ; from∘to = to∘from A≃B
    ; to∘from = from∘to A≃B
To show isomorphism is transitive, we compose the to and from functions, and use equational reasoning to combine the inverses:
≃-trans :  {A B C : Set}
   A  B
   B  C
   A  C
≃-trans A≃B B≃C =
    { to       = to   B≃C  to   A≃B
    ; from     = from A≃B  from B≃C
    ; from∘to  = λ{x 
          (from A≃B  from B≃C) ((to B≃C  to A≃B) x)
          from A≃B (from B≃C (to B≃C (to A≃B x)))
        ≡⟨ cong (from A≃B) (from∘to B≃C (to A≃B x)) 
          from A≃B (to A≃B x)
        ≡⟨ from∘to A≃B x 
    ; to∘from = λ{y 
          (to B≃C  to A≃B) ((from A≃B  from B≃C) y)
          to B≃C (to A≃B (from A≃B (from B≃C y)))
        ≡⟨ cong (to B≃C) (to∘from A≃B (from B≃C y)) 
          to B≃C (from B≃C y)
        ≡⟨ to∘from B≃C y 

Equational reasoning for isomorphism

It is straightforward to support a variant of equational reasoning for isomorphism. We essentially copy the previous definition of equality for isomorphism. We omit the form that corresponds to _≡⟨⟩_, since trivial isomorphisms arise far less often than trivial equalities:

module ≃-Reasoning where

  infix  1 ≃-begin_
  infixr 2 _≃⟨_⟩_
  infix  3 _≃-∎

  ≃-begin_ :  {A B : Set}
     A  B
     A  B
  ≃-begin A≃B = A≃B

  _≃⟨_⟩_ :  (A : Set) {B C : Set}
     A  B
     B  C
     A  C
  A ≃⟨ A≃B  B≃C = ≃-trans A≃B B≃C

  _≃-∎ :  (A : Set)
     A  A
  A ≃-∎ = ≃-refl

open ≃-Reasoning


We also need the notion of embedding, which is a weakening of isomorphism. While an isomorphism shows that two types are in one-to-one correspondence, an embedding shows that the first type is included in the second; or, equivalently, that there is a many-to-one correspondence between the second type and the first.

Here is the formal definition of embedding:
infix 0 _≲_
record _≲_ (A B : Set) : Set where
    to      : A  B
    from    : B  A
    from∘to :  (x : A)  from (to x)  x
open _≲_

It is the same as an isomorphism, save that it lacks the to∘from field. Hence, we know that from is left-inverse to to, but not that from is right-inverse to to.

Embedding is reflexive and transitive, but not symmetric. The proofs are cut down versions of the similar proofs for isomorphism:
≲-refl :  {A : Set}  A  A
≲-refl =
    { to      = λ{x  x}
    ; from    = λ{y  y}
    ; from∘to = λ{x  refl}

≲-trans :  {A B C : Set}  A  B  B  C  A  C
≲-trans A≲B B≲C =
    { to      = λ{x  to   B≲C (to   A≲B x)}
    ; from    = λ{y  from A≲B (from B≲C y)}
    ; from∘to = λ{x 
          from A≲B (from B≲C (to B≲C (to A≲B x)))
        ≡⟨ cong (from A≲B) (from∘to B≲C (to A≲B x)) 
          from A≲B (to A≲B x)
        ≡⟨ from∘to A≲B x 
It is also easy to see that if two types embed in each other, and the embedding functions correspond, then they are isomorphic. This is a weak form of anti-symmetry:
≲-antisym :  {A B : Set}
   (A≲B : A  B)
   (B≲A : B  A)
   (to A≲B  from B≲A)
   (from A≲B  to B≲A)
   A  B
≲-antisym A≲B B≲A to≡from from≡to =
    { to      = to A≲B
    ; from    = from A≲B
    ; from∘to = from∘to A≲B
    ; to∘from = λ{y 
          to A≲B (from A≲B y)
        ≡⟨ cong (to A≲B) (cong-app from≡to y) 
          to A≲B (to B≲A y)
        ≡⟨ cong-app to≡from (to B≲A y) 
          from B≲A (to B≲A y)
        ≡⟨ from∘to B≲A y 

The first three components are copied from the embedding, while the last combines the left inverse of B ≲ A with the equivalences of the to and from components from the two embeddings to obtain the right inverse of the isomorphism.

Equational reasoning for embedding

We can also support tabular reasoning for embedding, analogous to that used for isomorphism:

module ≲-Reasoning where

  infix  1 ≲-begin_
  infixr 2 _≲⟨_⟩_
  infix  3 _≲-∎

  ≲-begin_ :  {A B : Set}
     A  B
     A  B
  ≲-begin A≲B = A≲B

  _≲⟨_⟩_ :  (A : Set) {B C : Set}
     A  B
     B  C
     A  C
  A ≲⟨ A≲B  B≲C = ≲-trans A≲B B≲C

  _≲-∎ :  (A : Set)
     A  A
  A ≲-∎ = ≲-refl

open ≲-Reasoning

Exercise ≃-implies-≲ (practice)

Show that every isomorphism implies an embedding.
  ≃-implies-≲ :  {A B : Set}
     A  B
     A  B
-- Your code goes here

Exercise _⇔_ (practice)

Define equivalence of propositions (also known as “if and only if”) as follows:
record _⇔_ (A B : Set) : Set where
    to   : A  B
    from : B  A

Show that equivalence is reflexive, symmetric, and transitive.

-- Your code goes here

Exercise Bin-embedding (stretch)

Recall that Exercises Bin and Bin-laws define a datatype Bin of bitstrings representing natural numbers, and asks you to define the following functions and predicates:

to : ℕ → Bin
from : Bin → ℕ

which satisfy the following property:

from (to n) ≡ n
Using the above, establish that there is an embedding of into Bin.
-- Your code goes here

Why do to and from not form an isomorphism?

Standard library

Definitions similar to those in this chapter can be found in the standard library:
import Function using (_∘_)
import Function.Inverse using (_↔_)
import Function.LeftInverse using (_↞_)

The standard library _↔︎_ and _↞_ correspond to our _≃_ and _≲_, respectively, but those in the standard library are less convenient, since they depend on a nested record structure and are parameterised with regard to an arbitrary notion of equivalence.


This chapter uses the following unicode:

∘  U+2218  RING OPERATOR (\o, \circ, \comp)